Research on the inheritance, protection and development of Yang’s Taijiquan from the perspective of "intangible cultural heritage" - Zhao, Lulu (The Journal of the International Society of Chinese Health Practices, 2021)
In recent years, with the increasingly frequent economic globalization and cultural diversified exchanges, Chinese traditional sports projects have expanded their development space, but at the same time, they are also facing the impact of foreign sports culture, among which Taijiquan is affected. The protection of "intangible cultural heritage" (hereinafter referred to as "intangible cultural heritage") emerged in the late 20th century and early 21st century, and has been carried out for more than 20 years. Now the protection of "intangible cultural heritage" has been carried out in the world, and in China, a protection system of "protection first, rescue first, rational utilization, and inheritance and development" has been formed. "Intangible cultural heritage" is one of the important carriers of the Chinese nation spirit and national feelings, the basis of national unity and national unity, and also reflects the crystallization of the great wisdom of human beings. In the process of some martial arts projects being included in the "intangible cultural heritage", Taijiquan, as an important part of the traditional Chinese sports (martial arts projects), has attracted more attention, among which Yang’s Taijiquan is one of the first martial arts projects listed in the protection list of "intangible cultural heritage". As a representative brand of traditional sports and culture of the Chinese nation, Yang Style Taijiquan is facing severe challenges. Nowadays, how to better inherit and effectively protect the traditional Chinese traditional sports culture, and how to successfully develop China’s excellent traditional sports culture is the responsibility and obligation of every Chinese sons and daughters. This study aims to continue the return of Chinese traditional sports culture, improve the protection and development of Chinese intangible heritage projects, analyze the protection and development of other countries, and analyze the contemporary problems of inheritance, so as to ensure the sustainable development of Yang Taijiquan, and provide theoretical basis for the protection and development of Yang Taijiquan, in order to promote and promote the subsequent research. Methods: From the perspective of "intangible cultural heritage", this paper uses the literature research method, interview research method, comparative research method, logical analysis method and other scientific research methods to deeply study the inheritance, protection and development of Yang-style Taijiquan. Results: This study will conduct a general analysis from the following three aspects. 1. Comparative study on the protection and development of the intangible cultural heritage projects in China and other countries. On December 22, 2005, the State Council issued the Notice on Strengthening the Protection of Cultural Heritage, and formulated a 4-level protection system of "+ County, + Province", requiring local and relevant departments to implement the working policy of "protection first, rescue first, reasonable utilization, inheritance and development", and do a good job in the protection, management and reasonable utilization of intangible cultural heritage. On February 25, 2011, the 19th meeting of the Standing Committee of the 11th National People’s Congress adopted the Law of the People’s Republic of China; other countries have perfect protection measures for intangible cultural heritage projects, mainly showing: (1) the guiding role of the government. For example, Italy forms an "Italian protection model" that promotes the participation of all strata, the social protection adopted by the United States highlights the social participation, and France promotes the protection of intangible organizations at all levels under the leadership of the government. (2) The safeguard role of the law. Japan’s Cultural Finance Protection Law began in 1950, has been revised to meet the needs of social development; in 1962, Korea also formulated the Korean Cultural Finance Protection Law to protect the country’s intangible cultural heritage. The protection of intangible cultural heritage can be improved through the laws and regulations formulated, and these laws and regulations formulated by these countries can be used for the protection of intangible cultural heritage in China, so as to make corresponding contributions to the protection of intangible cultural heritage. (3) The basic role of the inheritor. South Korea’s cultural inheritor system is pyramid like our balanced dietary pagoda, and the top inheritor is called the "insured"; while the Japanese government selects the master "national treasure" in the national model and then protected by the government. Japan and South Korea pay attention to the protection of inheritors. economically, the government gives necessary support subsidies every year to guarantee the life of the inheritors; in society, improve the social status of the inheritors, and constantly encourage them to improve their skills and make efforts for the inheritance and development of world cultural heritage. (4) Auxiliary role of social institutions. For example, the intangible cultural heritage foundation established in Thailand; the protection of cultural heritage in Vietnam is undertaken by the Ministry of Cultural Information; and Mongolia. Through the establishment of these protection institutions, the state has realized the specialization to the protection of cultural heritage, with special organizations responsible for it, promoting the protection of the world cultural heritage. 2. At present, the main problems existing in the protection of "intangible cultural heritage" project are: (1) relevant laws and regulations are still not sound enough; (2) in the understanding and practice and legal construction, "cultural heritage" is replaced by "cultural relics", "the" cultural relics "protection is equivalent to the protection of the whole cultural heritage, so that the protection of" intangible cultural heritage " is not paid enough attention; (3) the protection of intangible cultural inheritors is not enough. In today’s education system, there is little professional knowledge about teaching and spreading the protection of "intangible cultural heritage". 3. At present, Taijiquan has spread to more than 160 countries and regions, becoming the project with the best communication effect, the widest communication range and the most practitioners among martial arts projects, and Yang Style Taijiquan is a typical representative. After consulting a large number of literature and materials, visiting folk boxing clubs, interviewing inheritors and practitioners learned that although Yang Taijiquan is popular in the world and become one of the most popular sports projects, some are also some shortcomings in the process of communication and development. The study found that there are the following problems in the process of Yang-style Taijiquan: (1) The inheritance concept is outdated. In the traditional martial arts culture, there has always been a narrow concept of valuing man over women, which is also the disadvantage of China’s social culture. Therefore, the master prefers man over women when teaching martial arts skills. The outdated concept leads to the decrease of the number of martial arts exercises, which is not conducive to the development of Yang Taijiquan; (2) the inheritance way is single. Yang’s Taijiquan is an important part of traditional martial arts. In its long process of development, mentoring inheritance has always been the main way of inheritance. The single way of inheritance leads to great limitations in the process of development, which cannot be spread well, thus restricting the development of Yang Taijiquan; (3) the lack of inheritors. In the inheritance of traditional martial arts, oral communication has always been an important form. Yang Taijiquan is an important part of traditional martial arts, and its inheritance and development cannot be separated from this form. In modern society, many inheritors belong to the state of suicide due to the lack of society. At the same time, in the process of master choosing the inheritors, the selection process is relatively strict. Due to various factors, the inheritors can not pass their skills to the next generation in time, which restricts the inheritance and development of Yang’s Taijiquan. Conclusion: In the development process of Yang’s Taijiquan, we should not only rely on some aspect of protection, but also coordinate the relationship between the national government, social organizations and individuals. First, in the foreign experience in the protection of "intangible cultural heritage", China should establish a complete legal system from the national level, the government should increase the importance of intangible cultural heritage; Secondly, to establish an effective protection institution at the social level to maximize their initiative; Finally, at the personal level to form an atmosphere of national participation. Through the importance of the state, the social response and the personal participation, so as to effectively promote the inheritance, protection and development of Yang-style Taijiquan.